COUNTERING THE NEXT PANDEMIC AFTER COVID-19: An Effort of Christian Education to Stop Phubbing - Sandy Ariawan (MAHABBAH: Journal of Religion and Education, 2022)
This research aims to see the magnitude of the influence of Christian education in the family on the potential of phubbing in students. The use of Information and Communication Technology (ICT) by households in Indonesia shows rapid development, followed by student delinquency rates that continue to increase. This is a quantitative research, using a measuring instrument in the form of a questionnaire, that was conducted on 300 respondents. The result showed that coeficient correlation between potency of Phubbing and Fatherlessness in Junior High School: 0,78; Senior High School: 0,72; and College: 0,76. Christian education in the family has a positive influence on the potential of phubbing in students. There are values that can be given special emphasis, which are able to overcome the pandemic after Covid-19, which is called phubbing. Thus, it is highly recommended for each family to implement: sticking to the standards of God, opening heart to be taught, and fearing the Lord.